The Social Life of Sardex and Liberex: Kin or Acquaintances? A Comparison Between Two Mutual Credit Circuits in Italy - Sartori, Laura (PARTECIPAZIONE E CONFLITTO, 2020)
We offer the first informed comparison of two regional mutual credit systems – Sardex and Liberex – aimed at sustaining the local economy. Building on previous research on Sardex, we develop an equivalent qualitative research investigating both organizers and members of the local circuit in Emilia Romagna. Within a theoretical framework that considers money as a social institution, socially and politically constructed, we first give an overview of the plurality of existing money pointing out a heated debate over the nature of money itself. Then, we move to evaluate whether the same monetary architecture – adopted by the two mutual credit systems – concretely comes with a similar social life. We confirm how social life of money is strictly intertwined with its monetary architecture by design, and discover how deeply it is also rooted in the institutional and relational contexts where it concretely operates. Money differs not only by nature and design, but also by context.